2017
DOI: 10.5014/ajot.2017.024802
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Supported Employment for People With Schizophrenia in Mainland China: A Randomized Controlled Trial

Abstract: Work-related social skills training embedded in ISE with generalization strategies can enhance vocational and nonvocational outcomes for people with schizophrenia in mainland China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(90 citation statements)
references
References 26 publications
1
87
0
Order By: Relevance
“…The majority of the study participants in both studies identified the relevance of work for persons with mental disorders and its role in the recovery process. The relevance of this finding has been previously recorded [39,40]. Mental healthcare providers who support employment for persons with mental illness in these settings offer both care and psycho-education.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The majority of the study participants in both studies identified the relevance of work for persons with mental disorders and its role in the recovery process. The relevance of this finding has been previously recorded [39,40]. Mental healthcare providers who support employment for persons with mental illness in these settings offer both care and psycho-education.…”
Section: Discussionsupporting
confidence: 62%
“…This would ensure that mechanisms that guard against discriminatory employment practices are in place and that dialogue and collaboration with employers is used to achieve fair employment practices. There is evidence in support of this finding and studies suggest that adoption of inclusive employment policies facilitates employment for persons with disorders [40,49]. Lastly, in order to improve employment opportunities for persons with mental disorders, government commitment to health care and social welfare is critical.…”
Section: Missingmentioning
confidence: 99%
“…Hoffmann et al and Howard et al and Heslin et al report the efficacy of IPS for the same patient population at two follow‐up periods, so we only included the latter study from both in our meta‐analysis. The meta‐analysis is based on 27 studies (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Where they exist and are taken up, they increase the employment opportunities for persons with a disability [13,38]. In this study, we observed three models of employment for persons with psychiatric disabilities.…”
Section: Other Facilitators Of Employability For People With Psychiatmentioning
confidence: 92%